Kesesuaian Penjatuhan Pidana Denda Dengan Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak Dalam Tindak Pidana Persetubuhan Oleh Anak - Naufalin Salma Allyanisa; Subekti Subekti; Riska Andi Fitriono (Hakim, 2024)
The aim of writing this article is to analyze the suitability of the imposition of fines by the panel of judges on children for the crime of sexual intercourse in the Karanganyar District Court decision Number 4/Pid.Sus-Anak/2023/PN.Krg with the Juvenile Criminal Justice System Law, especially in article 71 Paragraph (3) . The type of research used is normative with the nature of perspective research, while the approaches used are a case approach and a statutory approach. The results of this research are that the imposition of fines by judges is not in accordance with the Juvenile Criminal Justice System Law which clearly states that fines are replaced with job training.